Merged Banks and their Performance: A Study with Reference to Select Banks in India - K N, Usha (Journal of Neonatal Surgery, 2025)
Bank mergers were an important part of the early phases of the reforms to the financial sector that began in the early 1990s. Following the proposal of the broad pattern of the banking sector by the Narsimham Committee -1 (1991), the process of merger also gathered momentum. Committees on Fuller Capital Account Convertibility (2006), Financial Sector Assessment (2009), and the S.H. Khan Committee (1997) all went through the same consolidation procedure. (2009). Each of these groups came to the same conclusion: The Indian banking system needs to be reorganized, and it needs to be reorganized in a way that is market-driven, taking into account revenue and viability issues that are brought about by the M&A process. Therefore, the purpose of this research is to compare the efficiency of some merged Indian institutions before and after the mergers.